2023
DOI: 10.1017/s0261444823000046
|View full text |Cite
|
Sign up to set email alerts
|

Tangible insights on the strategizing of language learners and users

Abstract: This article presents reflections from 12 experts on language learners strategy (LLS) research. They were asked to offer their reflections in one of their domains of expertise, linking research into LLS with successful language learning and use practices. In essence, they were called upon to provide a review of recent scholarship by identifying areas where results of research had already led to the enhancement of learner strategy use, as well as to describe ongoing and future research efforts intended to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…It was already found that a single strategy cannot be used alone to complete a language task (Graham, 1997; Neubach & Cohen, 1988;Laviosa, 2000;Macaro, 2001Macaro, , 2003Macaro, , 2006Addamegh, 2003;Phakiti, 2006;Al Fraidan, 2019;Cohen et al, 2023a). This study aimed to further investigate the nature of the resultant clustering of TTS.…”
Section: Strategies Clusteringmentioning
confidence: 96%
See 4 more Smart Citations
“…It was already found that a single strategy cannot be used alone to complete a language task (Graham, 1997; Neubach & Cohen, 1988;Laviosa, 2000;Macaro, 2001Macaro, , 2003Macaro, , 2006Addamegh, 2003;Phakiti, 2006;Al Fraidan, 2019;Cohen et al, 2023a). This study aimed to further investigate the nature of the resultant clustering of TTS.…”
Section: Strategies Clusteringmentioning
confidence: 96%
“…Consequently, classifying them into a single functional category is deemed illogical. Cohen et al (2023a) propose the structure shown in Figure 2 to prove that strategy functions fluctuate. One strategy for determining the meaning of a word in a context can have four functions.…”
Section: Multifunctionality Of Strategiesmentioning
confidence: 99%
See 3 more Smart Citations